Urgensi Ilmu Mawaris dan Hukum Penerapannya dalam Praktik Kewarisan Islam - Mush'ab Bahrah (Universitas Cokroaminoto Yogyakarta, 2022)
Islamic inheritance law is often not properly understood or even misunderstood by many people. In particular, regarding the wisdom and urgency of the Islamic inheritance law, the obligation of obeying Islamic inheritance law, and whether or not it is permissible to divide inheritance not according to the sharia if all the heirs are agreed to it. By reviewing and analyzing data from various literary sources and with a syar'i norm approach, this research shows that the Islamic inheritance law has various wisdoms and urgency behind it. One of them is to regulate the distribution of inheritance which if not regulated by the sharia will certainly cause a lot of conflicts because humans will only rely on their respective minds which are of course very diverse and tend to be sbjective. This research also shows that it is obligatory to obey the Islamic inheritance law. As for if all the heirs agreed to share the inheritance as they wish, it is permissible as long as the heirs already know their respective share.